2006
DOI: 10.1002/pola.21509
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of polyimides bearing acid groups on long pendant aliphatic chains

Abstract: A series of novel polyimide electrolytes having long pendant sulfo-or phosphoalkoxy groups were synthesized for fuel-cell applications. Sulfodecyloxy-, phosphodecyloxy-, and sulfophenoxydodecyloxy-substituted benzidine monomers were synthesized from dihydroxybenzidine. These monomers were copolymerized with naphthalene tetracarboxylic dianhydride and fluorenylidene dianiline to give the corresponding polyimides. A flexible, ductile, and self-standing membrane was obtained via casting from the polyimide solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 20 publications
7
43
0
Order By: Relevance
“…The CÀ ÀS bonds are more likely to be thermally decomposed than the other side-chain bonds (e.g., CÀ ÀO bonds). These thermal properties are comparable to those of other sulfonated polyimides with shorter or longer aliphatic side chains, [18][19][20][21] and so we conclude that the phenylene rings introduced into the side chains do not practically affect the thermal stability.…”
Section: Polymer Synthesissupporting
confidence: 62%
See 2 more Smart Citations
“…The CÀ ÀS bonds are more likely to be thermally decomposed than the other side-chain bonds (e.g., CÀ ÀO bonds). These thermal properties are comparable to those of other sulfonated polyimides with shorter or longer aliphatic side chains, [18][19][20][21] and so we conclude that the phenylene rings introduced into the side chains do not practically affect the thermal stability.…”
Section: Polymer Synthesissupporting
confidence: 62%
“…Similar trends were observed for the even longer side chain polyimides. 21 Therefore, the most effective side-chain length seems to be three or four methylene units from the viewpoint of the proton-conducting properties.…”
Section: Hydrolytic and Oxidative Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these drawbacks, in recent years a number of alternative membranes have been developed [2][3][4][5][6][7][8][9][10][11]. Among the alternative materials investigated, sulphonated aromatic polymers, such as sulphonated poly(arylene sulphone)s [12][13][14][15], poly(arylene ether ketone)s [16][17][18][19][20], sulphonated poly(arylene ether sulphone)s [8,[21][22][23][24][25], polyimides [26][27][28][29], sulphonated poly(benzimidazole)s [30][31][32][33], have been proposed as alternative materials for PEMFCs. They show high proton conductivity, excellent thermal and oxidative stability, good mechanical properties, good processability, exceptional hydrolytic stability and relatively low cost.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Jannasch et al reported several side-group-acid poly-(ether sulfone)s with some attractive properties based on lithiation reaction. 24,31 Polyimides with side-group-acid substituents were also developed by Okamoto et al and Watanabe et al [32][33][34] To our knowledge, there are still no detailed reports related to the control of substitution sites through adjusting their various molecular structures. In addition, there are few reports of side-group-acid PEKs and their properties.…”
Section: Introductionmentioning
confidence: 99%